The Use of Expressions in Improving Kalam Skill in Learning Arabic for MTSN 2 Kediri Students - Jauharoh, Ervin; Anam, Wahidul; Huda, Mokhammad Miftakhul (UIN Syekh Wasil Kediri, Indonesia, 2021)
The purposes of this study were to find out the usage of expressions for improving speaking skill in teaching Arabic for students in the Islamic Junior High School 2 Kediri, and to know the effectiveness of it. The approach used for this research was a quantitative approach. As for the research method, it was the experimental method. The population in this research was the students in the Islamic Junior High School 2 Kediri in the 8th grade